O2-phase lithium cobalt oxide positive electrode material, preparation method thereof, positive electrode and battery
Through the synergistic action of doping and coating elements, the O2-phase lithium cobalt oxide positive electrode material is prepared, which solves the problem of structural instability of LiCoO2 at high voltage, achieves a high capacity, good cycling performance and a stable interface, and improves the energy density and life of the battery.
Patent Information
- Application Number
- CN202411782798.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
AI Technical Summary
The existing LiCoO2 positive electrode materials have structural instability at high voltages, resulting in capacity attenuation and interface side reactions, affecting their cycle life and energy density.
Through the synergistic action of doping and coating elements (M and A elements), O2-phase lithium cobalt oxide positive electrode material is prepared, reducing the presence of polycrystals and twins, improving the layer spacing, improving interface stability, and obtaining O2-phase lithium cobalt oxide with good electrochemical properties through molten salt ion exchange and lithium supplementation reaction.
The structural stability and interface stability of the O2-phase lithium cobalt oxide cathode material are achieved, and its capacity and circulation performance are improved, the cycle life is extended, and the energy density is improved.
Smart Images

Figure CN119601652A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to an O2-phase lithium cobalt oxide positive electrode material and a preparation method thereof, a positive electrode and a battery. Background Art
[0002] LiCoO2 layered cathode material was first reported by John B.Goodenough et al. in 1980. As a lithium-containing layered transition metal oxide, the layered structure of LiCoO2 is Li + It provides a 2D diffusion channel, has the characteristics of high specific capacity, high voltage platform, and better cycle stability, and has been widely used. The space group of conventional LiCoO2 is R-3m, composed of Li + and Co 3 + The layers are arranged alternately in the octahedral positions formed by the cubic close-packed O2-. The LiO6 and CoO6 octahedra are stacked with shared edges. The arrangement order of the O layers is ABCABC, which belongs to the O3 phase.
[0003] The theoretical capacity of O3 phase LiCoO2 is as high as 274mAh / g, which has a very high volume energy density, but the actual capacity release of LiCoO2 is closely related to the charging voltage. For example, at a cut-off voltage of 4.4V, it has a specific capacity of 170mAh / g and a volume energy density of 2820.3Wh / L, which is similar to the lower-priced high-nickel materials. To further improve the capacity performance and energy density of LiCoO2, it is necessary to continuously increase the charging voltage of LiCoO2; therefore, researchers have conducted extensive research on high-voltage LiCoO2. With various theoretical studies, coating and doping modifications, the voltage of LiCoO2 has been gradually increased, but when charged to 4.5V and above, the capacity attenuation mechanism of LiCoO2 in organic electrolytes becomes very complicated, which is not only related to the crystal structure and electronic structure of the material itself, but also to the type of electrolyte and interface properties. The O3→H 1-3 →O1 phase transition, the reversibility of the slip phase transition of the CoO2 layer is reduced, and the particles undergo a c-axis contraction of more than 3%; 3+ / 4+ The 3d energy band of O 2- The top of the 2p band overlaps, resulting in the O 2- It will provide charge compensation and cause oxidation reaction, and O will be released from the lattice, causing irreversible damage to the material. Some researchers have also found that when charged to a higher potential, the interface of LiCoO2 is unstable and a spinel phase with low electrochemical activity will be generated; in addition, some researchers believe that certain solvents in the organic electrolyte will react with the surface of LiCoO2, causing the LiCoO2 interface to change or even dissolve.
[0004] Therefore, developing LiCoO2 cathode materials that are more stable and have higher energy density at high voltages is the current mainstream research direction. O2 phase LiCoO2 has a different spatial arrangement from O3 phase LiCoO2, but can still maintain a stable crystal structure at a higher delithiation state. The CoO6 octahedron in the O2 phase LiCoO2 has a stronger Co-O bond, which enhances the structural stability to resist proton attack and prolongs the cycle life in aqueous electrolytes. In addition, the O2 phase LiCoO2 undergoes a reversible phase change during the cycle process and will not be converted into the more thermodynamically stable O3 phase LiCoO2 or spinel phase. Combined with the above advantages, O2 phase LiCoO2 can be used as a very potential synthesis path for LiCoO2 cathode materials at high voltages. The currently disclosed preparation methods include first preparing a sodium cobalt oxide precursor and then preparing the O2 phase LiCoO2 by molten salt ion exchange, but due to its complex exchange mechanism and influence on the interface, the interface stability of the particles is inferior to that of traditional lithium cobalt oxide materials.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide an O2 phase lithium cobalt oxide positive electrode material and a preparation method thereof, a positive electrode and a battery, aiming to provide an O2 phase lithium cobalt oxide with good electrochemical performance, and a preparation method that can inhibit the bulk slip of the O2 phase lithium cobalt oxide during charging and discharging and improve the interface stability.
[0007] The present invention is achieved in that:
[0008] In the first aspect, the present invention provides an O2 phase lithium cobalt oxide positive electrode material, the chemical formula of the lithium cobalt oxide positive electrode material is Li a Na b Co c M d A e O 2-f X f , M is selected from any one or more of Mg, Al, W, Ti, La, Zr, Y, Ni, Mn, K, and Te, A is selected from any one or more of Mg, Al, W, Ti, La, Zr, Y, Ni, Mn, K, and Te, and X is selected from at least one of B, F, and Cl, wherein 0.9≤a≤1, 0≤b≤0.01, 0.95≤c≤1, 0≤d≤0.05, 0≤e≤0.01, and 0≤f≤0.01.
[0009] In an optional embodiment, the invention further comprises at least one of the following technical features (1) to (4):
[0010] (1) The molar ratio of lithium to cobalt in the O2 phase lithium cobalt oxide positive electrode material is 0.9 to 1.0:1;
[0011] (2) The median particle size Dv50 of the O2 phase lithium cobalt oxide positive electrode material is 5.0 to 8.0 μm;
[0012] (3) The main peak of the XRD spectrum of the O2 phase lithium cobalt oxide cathode material is located at 18.6±0.1°;
[0013] (4) The ratio of the area of the (002) peak to the area of the (103) peak in the XRD spectrum of the O2 phase lithium cobalt oxide positive electrode material particles is 2.5 to 3.5:1.
[0014] In a second aspect, the present invention provides a method for preparing an O2-phase lithium cobalt oxide positive electrode material, comprising:
[0015] The mixture is subjected to a first solid phase sintering, wherein the mixture includes sodium, cobalt and M elements, and a sodium cobaltate precursor is obtained after sintering, wherein the molar ratio of the sodium element to the cobalt element in the mixture is 0.65 to 1:1;
[0016] The sodium cobaltate precursor and the coating material are mixed evenly and then solid-phase sintered for the second time to obtain a precursor with a coating layer, wherein the coating material contains cobalt element and A element;
[0017] After uniformly mixing the precursor with the coating layer and the first lithium source, molten salt ion exchange is performed, and after impurities are removed, a T2&O2 composite lithium cobalt oxide material is obtained;
[0018] The T2&O2 composite lithium cobalt oxide material and the second lithium source are dispersed in water to carry out a lithium supplementation reaction to obtain an O2 phase lithium cobalt oxide positive electrode material.
[0019] In an optional embodiment, the cobalt element in the mixture is provided by a first cobalt source, and the first cobalt source is selected from at least one of cobalt tetroxide, cobalt hydroxide, cobaltous hydroxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide;
[0020] Optionally, the M element is doped into the first cobalt source.
[0021] In an optional embodiment, the sodium element in the mixture is provided by a sodium source, and the sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate.
[0022] In an optional embodiment, at least one of the following technical features (1) to (10) is included;
[0023] (1) The sintering conditions of the first solid phase sintering are: heating to 700-900°C at 1-10°C / min and keeping at this temperature for 8-30h;
[0024] (2) The sintering conditions of the second solid phase sintering are: heating to 500-700°C at 1-10°C / min and keeping at this temperature for 8-30h;
[0025] (3) The conditions for molten salt ion exchange are: heating to 180-300°C at 1-10°C / min and keeping warm for 0.5-12h;
[0026] (4) the first lithium source is composed of at least two of LiNO3, LiCl, Li2CO3, LiOH, Li2SO4, Li3PO4, and CH3COOLi;
[0027] (5) the molar ratio of the lithium element in the first lithium source to the sodium element in the precursor having the coating layer is 1.4 to 20:1;
[0028] (6) The mass ratio of the T2&O2 composite lithium cobalt oxide material to the second lithium source is 1:2-3;
[0029] (7) The mass ratio of T2&O2 composite lithium cobalt oxide material to water is 2-3:14-20;
[0030] (8) the second lithium source is selected from at least one of lithium hydroxide, lithium carbonate and lithium chloride;
[0031] (9) The cobalt element in the coating material is provided by a second cobalt source, and the second cobalt source is selected from at least one of cobaltous hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide;
[0032] (10) The A element in the coating material is provided by a compound containing the A element.
[0033] In an optional embodiment, the impurity removal method includes: washing the molten salt ion exchange product with water and then drying it to obtain a T2&O2 composite lithium cobalt oxide material.
[0034] In an optional embodiment, after the lithium supplementation reaction, the finished product is extracted from the mixed system, and the extraction method includes: solid-liquid separation, water washing and drying.
[0035] In a third aspect, the present invention provides a positive electrode, the active component of which includes an O2-phase lithium cobalt oxide positive electrode material as described in the aforementioned embodiment, or an O2-phase lithium cobalt oxide positive electrode material prepared by the preparation method of any one of the aforementioned embodiments.
[0036] In a fourth aspect, the present invention provides a battery, comprising the positive electrode according to the aforementioned embodiment.
[0037] The present invention has the following beneficial effects:
[0038] The O2-phase lithium cobalt oxide positive electrode material provided by the present invention can reduce the presence of polycrystals and twins, improve the interlayer spacing, reduce the content of residual Na and stabilize the bulk structure under the synergistic effect of doping and coating elements (M and A elements), and can also improve the stability of the interface, inhibit the occurrence of interfacial side reactions, and at the same time give the O2-phase lithium cobalt oxide positive electrode material good capacity and cycle performance.
[0039] The preparation method provided by the present invention can achieve uniform distribution of different doping and coating elements, fully complete the exchange of lithium ions and sodium ions, reduce residual sodium ions, and further obtain O2 phase lithium cobalt oxide through a simple lithium supplementation operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0041] Figure 1 This is a SEM image of the sodium cobaltate precursor during the preparation process of Example 1;
[0042] Figure 2 This is a SEM image of the precursor with a coating layer prepared in Example 1;
[0043] Figure 3 This is a SEM image of the O2-phase lithium cobalt oxide positive electrode material prepared in Example 1;
[0044] Figure 4 This is the XRD diagram of the O2 phase lithium cobalt oxide positive electrode material prepared in Example 1. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0046] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0047] An O2-phase lithium cobalt oxide positive electrode material provided in an embodiment of the present invention has a chemical formula of Li a Na b Co c M d A eO 2-f X f , M is selected from any one or more of Mg, Al, W, Ti, La, Zr, Y, Ni, Mn, K, and Te, A is selected from any one or more of Mg, Al, W, Ti, La, Zr, Y, Ni, Mn, K, and Te, and X is selected from at least one of B, F, and Cl, wherein 0.9≤a≤1, 0≤b≤0.01, 0.95≤c≤1, 0≤d≤0.05, 0≤e≤0.01, and 0≤f≤0.01.
[0048] The O2 phase lithium cobalt oxide positive electrode material provided by the present invention has a stronger Co-O bond and better structural stability than O3 phase lithium cobalt oxide. Under the synergistic effect of doping and coating elements (M and A elements), the O2 phase lithium cobalt oxide positive electrode material can not only reduce the presence of polycrystals and twins, improve the interlayer spacing, reduce the residual Na content and stabilize the bulk structure, but also improve the stability of the interface, inhibit the occurrence of interfacial side reactions, and at the same time give the O2 phase lithium cobalt oxide positive electrode material good capacity and cycle performance.
[0049] Optionally, the main peak of the XRD spectrum of the O2 phase lithium cobalt oxide positive electrode material is located at 18.6±0.1°.
[0050] Optionally, the ratio of the area of the (002) peak to the area of the (103) peak in the XRD spectrum of the O2 phase lithium cobalt oxide positive electrode material particles is 2.5 to 3.5: 1. The main peak of the XRD spectrum of the present invention is consistent with the main peak position of PDF#36-1004, indicating that the lithium cobalt oxide described in the present invention is O2 phase lithium cobalt oxide, and the area ratio of 002 to 103 is 2.5 to 3.5: 1, indicating that the crystallinity of the O2 phase lithium cobalt oxide is good, which can prevent the crystal structure of the O2 phase lithium cobalt oxide from slipping during the charge and discharge process and maintain the stability of the structure.
[0051] Optionally, in order to further improve the electrochemical performance of the O2 phase lithium cobalt oxide positive electrode material, the molar ratio of lithium element and cobalt element contained therein is 0.9 to 1:1.
[0052] Optionally, in order to further improve the electrochemical performance of the O2 phase lithium cobalt oxide positive electrode material, the median particle size Dv50 of the O2 phase lithium cobalt oxide positive electrode material is 5.0 to 8.0 μm.
[0053] The method for preparing an O2-phase lithium cobalt oxide positive electrode material provided in an embodiment of the present invention comprises:
[0054] The mixture is subjected to a first solid phase sintering, wherein the mixture includes sodium, cobalt and M elements, and a sodium cobaltate precursor is obtained after sintering, wherein the molar ratio of the sodium element to the cobalt element in the mixture is 0.65 to 1:1;
[0055] The sodium cobaltate precursor and the coating material are mixed evenly and then solid-phase sintered for the second time to obtain a precursor with a coating layer, wherein the coating material contains cobalt element and A element;
[0056] After uniformly mixing the precursor with the coating layer and the first lithium source, molten salt ion exchange is performed, and after impurities are removed, a T2&O2 composite lithium cobalt oxide material is obtained;
[0057] The T2&O2 composite lithium cobalt oxide material and the second lithium source are dispersed in water to perform a lithium supplementation reaction to obtain an O2 phase lithium cobalt oxide positive electrode material;
[0058] M is selected from any one or more of Mg, Al, W, Ti, La, Zr, Y, Ni, Mn, K, and Te elements; A is selected from any one or more of Mg, Al, W, Ti, La, Zr, Y, Ni, Mn, K, and Te elements.
[0059] The preparation method provided by the present invention can achieve uniform distribution of different doping and coating elements, fully complete the exchange of lithium ions and sodium ions, reduce residual sodium ions, and further obtain O2 phase lithium cobalt oxide through a simple lithium supplementation operation.
[0060] Specifically, the preparation method is:
[0061] S1. First solid phase sintering
[0062] The various raw materials are uniformly mixed to obtain a mixture, wherein the mixture includes sodium and cobalt, and the molar ratio of the sodium to the cobalt element is 0.65 to 1:1 (for example, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.9:1 or 1:1); preferably, the molar ratio of the sodium to the cobalt element is 0.65 to 0.85:1 (for example, 0.65:1, 0.75:1, 0.8:1 or 0.85:1);
[0063] The mixture is heated to 700-900°C (e.g. 700°C, 800°C or 900°C) at 1-10°C / min (e.g. 1°C / min, 5°C / min or 10°C / min), kept warm for 8-30h (e.g. 8h, 10h, 20h, or 30h), and then cooled in the furnace to obtain a sodium cobaltate precursor. The sodium cobaltate precursor is ground and sieved to obtain a powder with a particle size of 6.0-9.5μm for standby use. The space group of the sodium cobaltate precursor is P63 / mmc.
[0064] Optionally, the raw material includes a first cobalt source, and the first cobalt source is selected from at least one of cobalt tetroxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide;
[0065] Optionally, the mixture also includes element M, and M is selected from at least one of Al, Mg, W, Ti, La, Zr, Y, Ni, Mn, K, and Te.
[0066] Optionally, the M element is doped in the first cobalt source, or the M element is a metal oxide, metal hydroxide, carbonate, sulfate, nitrate or a single substance that is mixed alone.
[0067] Optionally, the raw materials for obtaining the mixture include a sodium source, and the sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate.
[0068] S2, second solid phase sintering
[0069] The powdered sodium cobalt oxide precursor obtained in S1 is evenly mixed with a coating material, wherein the coating material contains cobalt element and A element;
[0070] After mixing evenly, the mixture is heated to 500-700°C (for example, 500°C, 550°C, 600°C, 650°C or 700°C) at a rate of 1-10°C / min (for example, 1°C / min, 5°C / min or 1°C / min), and kept warm for 8-30h (for example, 8h, 10h, 15h, 20h or 30h). During the entire sintering process, the residual sodium on the surface of the sodium cobaltate precursor reacts with the cobalt element and the A element in the coating material, and a precursor with a coating layer is obtained as the furnace is cooled. The coating layer of the precursor with a coating layer may be a uniform coating or an island coating. In addition, part of the coating material will penetrate into the sodium cobaltate precursor during the sintering process.
[0071] Optionally, the coating material includes a second cobalt source and a compound of element A. The second cobalt source is selected from at least one of cobaltous hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide.
[0072] Optionally, the amount of cobalt source is 0.2% to 10% (e.g., 0.2%, 1%, 3%, 5%, 8% or 10%) of the mass of the sodium cobaltate precursor, and the amount of the compound of element A is 0.05% to 5% (e.g., 0.05%, 0.1%, 1%, 2% or 5%) of the mass of the sodium cobaltate precursor.
[0073] S3, molten salt ion exchange
[0074] The precursor with the coating layer obtained in S2 is mixed evenly with the first lithium source, and then the temperature is raised to 180-300°C (for example, 180°C, 200°C, 250°C or 300°C) at 1-10°C / min (for example, 1°C / min, 5°C / min or 1°C / min), and the temperature is kept for 0.5-12h (for example, 0.5h, 1h, 3h, 5h, 8h, 10h or 12h) for molten salt ion exchange, and the crude composite phase lithium cobalt oxide material is obtained after cooling with the furnace. The space group of the T2 phase structure is Cmca, and the space group of the O2 phase structure is P63mc.
[0075] Optionally, to ensure sufficient exchange of lithium ions and sodium ions, an excess lithium source is usually used, for example, the molar ratio of the lithium element in the first lithium source involved in the mixture to the sodium element in the precursor having the coating layer is 1.4 to 20:1 (e.g., 1.4:1, 2:1, 5:1, 10:1, 15:1 or 20:1).
[0076] The obtained crude composite phase lithium cobalt oxide material is de-impurified to obtain T2&O2 composite lithium cobalt oxide material.
[0077] The impurity removal is mainly to remove the sodium ions released after ion exchange and the remaining lithium source when the lithium source is used excessively in the previous step.
[0078] Optionally, the impurity removal method is washing with water followed by drying.
[0079] Optionally, the drying temperature is 80-150° C. (eg, 80° C., 100° C., 120° C. or 150° C.), and the drying time is ≥12 h.
[0080] S4. Lithium supplement
[0081] The T2&O2 composite lithium cobalt oxide material obtained in S3 is dispersed in deionized water, and a second lithium source is added thereto and stirred to mix well, ensuring that the mixed system is in a closed environment. The reaction temperature is controlled to be 90-110°C (for example, 90°C, 100°C or 110), and the lithium replenishment reaction is allowed to stand for 18-24h (for example, 18h, 20h or 24h) to transform the T2&O2 composite phase into the O2 phase.
[0082] The reaction system is subjected to solid-liquid separation to obtain crude O2 lithium cobalt oxide;
[0083] The crude O2 lithium cobalt oxide is washed with water at least once to remove impurities, and then dried to obtain a finished O2 phase lithium cobalt oxide positive electrode material, in which the molar ratio of lithium element to cobalt element is 0.9 to 1:1 (e.g., 0.9:1, 0.95:1 or 1:1).
[0084] Optionally, to ensure that the T2 phase can be fully transformed into the O2 phase, the mass ratio of the T2&O2 composite lithium cobalt oxide material to the second lithium source is 1:2 to 3 (e.g., 1:2, 1:2.5 or 1:3);
[0085] Optionally, in order to better disperse the T2&O2 composite lithium cobalt oxide material, the mass ratio of the T2&O2 composite lithium cobalt oxide material to deionized water is 2 to 3:14 to 20 (for example, 2:14, 2:17, 2:20, 3:14, 3:18 or 3:20).
[0086] Optionally, the second lithium source is selected from at least one of lithium hydroxide, lithium carbonate and lithium chloride.
[0087] An embodiment of the present invention provides a positive electrode, the active component of which includes the O2 phase lithium cobalt oxide positive electrode material provided by the embodiment of the present invention, or the O2 phase lithium cobalt oxide positive electrode material prepared by the preparation method provided by the embodiment of the present invention.
[0088] The battery provided by the embodiment of the present invention includes the positive electrode provided by the embodiment of the present invention.
[0089] Example 1
[0090] (1) Na2CO3 with D50=4.5 μm and Y-doped Co3O4 with D50=7.5 μm (Y element accounts for 0.005 of the total molar amount of metal elements in cobalt tetroxide) are uniformly mixed at a Na / Co molar ratio of 0.75:1 and then sintered at high temperature. The sintering process is to increase the temperature to 800°C at 3.5°C / min, keep the temperature for 15 hours, cool with the furnace, grind and sieve to obtain a sodium cobalt oxide precursor with D50=6.5 μm, such as Figure 1 As shown in the figure, it can be seen that the sodium cobalt oxide precursor is close to an amorphous structure, and the particle surface is relatively rough;
[0091] (2) The prepared sodium cobaltate precursor was uniformly mixed with 8 wt% of cobaltous oxide and 0.4 wt% of aluminum oxide in an amount equal to 8 wt% of the sodium cobaltate precursor, and the mixture was sintered at a temperature of 4°C / min to 700°C, kept at that temperature for 12 h, cooled with the furnace, ground and sieved to obtain a coated precursor with a Dv50 of 8.752 μm;
[0092] (3) The coated precursor and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 12:1, wherein the molar ratio of LiNO3:LiCl is 70:30, and then ion exchange is performed. The ion exchange conditions are heating to 220°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing with water and drying to obtain a T2&O2 phase composite lithium cobalt oxide material;
[0093] (4) The T2&O2 composite lithium cobalt oxide material is uniformly dispersed in deionized water, and lithium hydroxide is added, wherein the mass ratio of the T2&O2 composite lithium cobalt oxide material, lithium hydroxide and deionized water is 1:2.5:20. After mixing, the mixture is placed in a sealed container, and allowed to stand in an oven at 100°C for 24 hours, and then washed and dried to obtain O2 phase lithium cobalt oxide.
[0094] The chemical formula of the prepared O2 phase lithium cobalt oxide is Li 0.98 Na 0.0003 Y 0.00032 Al 0.0001 Co 0.9998 O 1.9995 Cl 0.0005 The median particle size of the material is 6.43 μm, and the molar ratio of lithium to cobalt is 0.9802. The SEM image of the prepared O2 phase lithium cobalt oxide is as follows: Figure 3 and Figure 4 As shown in the figure, it can be seen that the prepared samples are flat, amorphous particles with smooth surfaces, and a small number of particles have cracks. Figure 4 As shown in the figure, it can be seen that the main peak position of the XRD spectrum of the O2 phase lithium cobalt oxide positive electrode material is 18.63, and the ratio of the area of the 002 peak to the area of the 103 peak is 3.1:1.
[0095] Example 2
[0096] (1) Na2CO3 with D50=5.4μm and Y&Mg-doped Co3O4 with D50=7.5μm (Y element accounts for 0.005 of the total molar amount of metal elements in cobalt oxide, and Mg element accounts for 0.01 of the total molar amount of metal elements in cobalt oxide) are uniformly mixed at a Na / Co molar ratio of 0.75, and then sintered at high temperature. The sintering process is to increase the temperature to 810°C at 4°C / min, keep the temperature for 16h, cool with the furnace, grind and sieve to obtain a sodium cobalt oxide precursor with D50=8.1μm;
[0097] (2) uniformly mixing the prepared sodium cobaltate precursor with 1 wt% of aluminum oxide, 0.5 wt% of magnesium fluoride and 5 wt% of cobalt nitrate in an amount to the precursor, sintering the mixture at a temperature of 4°C / min to 600°C, keeping the temperature for 12 hours, cooling the mixture with the furnace, grinding and sieving the mixture to obtain a coated sodium cobaltate precursor;
[0098] (3) The coated sodium cobalt oxide precursor and lithium nitrate and lithium hydroxide are uniformly mixed in a Li / Na molar ratio of 8:1, wherein the molar ratio of LiNO3:LiOH is 75:25, and then ion exchange is carried out. The ion exchange conditions are heating to 250°C at 4°C / min, keeping warm for 1h, cooling with the furnace, washing with water and drying to obtain a T2&O2 (O2 phase accounts for >90%) phase composite lithium cobalt oxide material.
[0099] (4) The T2&O2 composite lithium cobalt oxide material is uniformly dispersed in deionized water, and lithium hydroxide is added, wherein the mass ratio of the T2&O2 composite lithium cobalt oxide material, lithium hydroxide and deionized water is 1:2.1:20. After mixing, it is placed in a sealed container, and allowed to stand in an oven at 100°C for 22 hours, and then washed and dried to obtain O2 phase lithium cobalt oxide.
[0100] The main chemical formula of the prepared O2 phase lithium cobalt oxide is Li 0.99 Na 0.0002 Y 0.0003 Mg 0.0004 Al 0.0001 Co 0.999 O 1.99 8F 0.0015 Cl 0.0005 The median particle size of the material is 7.02 μm, and the molar ratio of lithium to cobalt is 0.99.
[0101] Example 3
[0102] (1) Na2CO3 with D50=5.4 μm and Y&Al-doped Co3O4 with D50=7.5 μm (Y element accounts for 0.01 of the total molar amount of metal elements in cobalt oxide, and Al element accounts for 0.01 of the total molar amount of metal elements in cobalt oxide) are uniformly mixed at a Na / Co molar ratio of 0.75:1 and then sintered at high temperature. The sintering process is to increase the temperature to 830°C at 4°C / min, keep the temperature for 13 hours, cool with the furnace, grind and sieve to obtain a sodium cobalt oxide precursor with D50=8.21 μm;
[0103] (2) The prepared sodium cobaltate precursor is uniformly mixed with 5wt% of cobalt hydroxide oxide, 0.6wt% of aluminum oxide, and 0.3% of lanthanum oxide in an addition ratio of 5wt% to the precursor, and the sintering process is to increase the temperature to 650°C at 4°C / min, keep the temperature for 12h, cool with the furnace, grind and sieve to obtain a coated sodium cobaltate precursor with D50=7.52μm.
[0104] (3) The coated sodium cobalt oxide precursor and lithium carbonate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 4:1, wherein the molar ratio of Li2CO3:LiCl is 65:35, and then ion exchange is performed. The ion exchange conditions are heating to 230°C at 4°C / min, keeping warm for 1h, cooling with the furnace, washing with water and drying to obtain a T2&O2 (O2 phase accounts for >90%) phase composite lithium cobalt oxide material;
[0105] (4) The T2&O2 composite lithium cobalt oxide material is uniformly dispersed in deionized water, and lithium hydroxide is added, wherein the mass ratio of the T2&O2 composite lithium cobalt oxide material, lithium hydroxide and deionized water is 1:2.3:16. The solution is placed in a sealed container, and allowed to stand in an oven at 95°C for 24 hours, and then washed and dried to obtain O2 phase lithium cobalt oxide.
[0106] The main chemical formula of the prepared O2 phase lithium cobalt oxide is Li 0.99 Na 0.002 Y 0.004 Al 0.004 Co 0.99 O1.9995 Cl 0.0005 The median particle size of the material is 5.78 μm, and the molar ratio of lithium to cobalt is 1.0.
[0107] Comparative Example 1
[0108] Li2CO3 with D50=4.5μm and Co3O4 with D50=16.5μm were uniformly mixed in a Li / Co molar ratio of 1.05 and then sintered at high temperature. The sintering process was as follows: heating to 750℃ at 4℃ / min, keeping the temperature for 3h, then heating to 1050℃ at 2℃ / min, keeping the temperature for 6.5h, cooling with the furnace, grinding and sieving to obtain conventional O3 phase lithium cobalt oxide with D50=5.02μm.
[0109] Comparative Example 2
[0110] The only difference between this comparative example and Example 1 is that the coating of the sodium cobaltate precursor in step 2 is not performed.
[0111] (1) Na2CO3 and Co3O4 were uniformly mixed in a Na / Co molar ratio of 0.75:1 and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 3.5°C / min, keep the temperature for 15 hours, cool with the furnace, grind and sieve to obtain a sodium cobalt oxide precursor with a D50 of 6.54 μm.
[0112] (2) uniformly mixing a sodium cobalt oxide precursor, lithium nitrate and lithium chloride at a Li / Na molar ratio of 12:1, wherein the molar ratio of LiNO3:LiCl is 70:30, and then performing ion exchange under the conditions of heating to 220°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing with water and drying to obtain a T2&O2 phase composite lithium cobalt oxide material;
[0113] (3) The T2&O2 composite lithium cobalt oxide material is uniformly dispersed in deionized water, and lithium hydroxide is added, wherein the mass ratio of the T2&O2 composite lithium cobalt oxide material, lithium hydroxide and deionized water is 1:2.5:20, and the solution is placed in a sealed container, and placed in an oven at 100°C for 24 hours, and then washed and dried to obtain O2 phase lithium cobalt oxide. The chemical formula of the prepared O2 phase lithium cobalt oxide is Li 0.99 Na 0.000 2Y 0.0003 Co 0.99 O 1.9998 Cl 0.0002 .
[0114] Comparative Example 3
[0115] The difference between this comparative example and Example 1 is that the cobalt tetroxide in step 1 is undoped.
[0116] (1) Na2CO3 with D50=4.5 μm and Co3O4 with D50=7.5 μm were uniformly mixed in a Na / Co molar ratio of 0.75:1 and then sintered at high temperature. The sintering process was to increase the temperature to 800°C at 3.5°C / min, keep the temperature for 15 hours, cool with the furnace, grind and sieve to obtain a sodium cobalt oxide precursor with D50=6.52 μm;
[0117] (2) The prepared sodium cobaltate precursor was uniformly mixed with 8 wt% of cobaltous oxide and 0.4 wt% of aluminum oxide in an amount equal to 8 wt% of the sodium cobaltate precursor, and the mixture was sintered at a temperature of 4 °C / min to 700 °C, kept at that temperature for 12 h, cooled with the furnace, ground and sieved to obtain a coated precursor with a D50 of 8.752 μm;
[0118] (3) The coated precursor and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 12:1, wherein the molar ratio of LiNO3:LiCl is 70:30, and then ion exchange is performed. The ion exchange conditions are heating to 220°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing with water and drying to obtain a T2&O2 phase composite lithium cobalt oxide material;
[0119] (4) The T2&O2 composite lithium cobalt oxide material is uniformly dispersed in deionized water, and lithium hydroxide is added, wherein the mass ratio of the T2&O2 composite lithium cobalt oxide material, lithium hydroxide and deionized water is 1:2.5:20. After mixing, the mixture is placed in a sealed container, and allowed to stand in an oven at 100°C for 24 hours, and then washed and dried to obtain O2 phase lithium cobalt oxide.
[0120] The main chemical formula of the prepared O2 phase lithium cobalt oxide is Li 0.99 Na 0.0002 Al 0.0002 Co 0.9994 O 1.9995 Cl 0.0005 .
[0121] Comparative Example 4
[0122] (1) Na2CO3 with D50=4.5 μm and Y-doped Co3O4 with D50=7.5 μm (Y element accounts for 0.005 of the total molar amount of metal elements in cobalt tetroxide) are uniformly mixed at a Na / Co molar ratio of 0.75:1 and then sintered at high temperature. The sintering process is to increase the temperature to 800°C at 3.5°C / min, keep the temperature for 15 hours, cool with the furnace, grind and sieve to obtain a sodium cobalt oxide precursor with D50=6.5 μm;
[0123] (2) The prepared sodium cobaltate precursor was uniformly mixed with 8 wt% of cobaltous oxide and 0.4 wt% of aluminum oxide in an amount equal to 8 wt% of the sodium cobaltate precursor, and the mixture was sintered at a temperature of 4 °C / min to 700 °C, kept at that temperature for 12 h, cooled with the furnace, ground and sieved to obtain a coated precursor with a D50 of 8.752 μm;
[0124] (3) The coated precursor and lithium nitrate and lithium chloride are uniformly mixed in a Li / Na molar ratio of 12:1, wherein the molar ratio of LiNO3:LiCl is 70:30, and then ion exchange is performed. The ion exchange conditions are heating to 220°C at 4°C / min, keeping the temperature for 1h, cooling with the furnace, washing with water and drying to obtain a T2&O2 phase composite lithium cobalt oxide material; the chemical formula of the T2&O2 phase composite lithium cobalt oxide material is Li 0.72 Na 0.0002 Al 0.0002 Co 0.9998 O 1.9995 Cl 0.0005 .
[0125] Experimental example
[0126] The present invention adopts a particle size tester to test the median particle size Dv50 of the lithium cobalt oxide material, and adopts an inductively coupled plasma tester to test the molar ratio of the lithium element and the cobalt element of the lithium cobalt oxide material.
[0127] The positive electrode materials prepared in Examples 1-3 and Comparative Examples 1 to 4 are used as positive electrode active materials, Super P is a conductive agent, polyvinylidene fluoride (PVDF) is a binder, and the mass ratio of the above three is 90:5:5. An appropriate amount of N-methylpyrrolidone (NMP) is added to control the solid content of the slurry to 45%, and the slurry is evenly mixed and applied to the aluminum foil current collector. After vacuum drying, it is taken out and hot pressed, and cut into a positive electrode sheet with a diameter of 12mm and a thickness of about 45μm. The button lithium-ion battery is assembled from the above-mentioned positive electrode sheet, lithium sheet negative electrode, separator between the positive and negative electrodes, and electrolyte. The assembled battery is placed in a 45℃ high and low temperature box, and a constant current charge and discharge cycle test is performed on the Xinwei battery test channel. The test conditions are: charge and discharge cut-off voltage 3.0-4.65V (vs Li+ / Li), the first cycle charge and discharge rate is 0.1C, the second cycle charge and discharge rate is 0.2C, and the cycle is 50 cycles. The test results are shown in Table 1.
[0128] Table 1 Comparison of electrochemical performance of examples and comparative examples
[0129]
[0130]
[0131] It can be seen from Table 1 that the lithium cobalt oxide positive electrode materials prepared in various embodiments of the present invention have better electrochemical properties after being made into batteries, and have better performance than the conventional O3 phase lithium cobalt oxide (Comparative Example 1) positive electrode material.
[0132] Comparing Example 1 with Comparative Example 2, the capacity retention rate of Example 1 is significantly higher than that of Comparative Example 2, indicating that it is difficult to obtain a positive electrode material with a high capacity retention rate if the precursor is not coated during the preparation process;
[0133] Comparing Example 1 with Comparative Example 3, the capacity and cycle retention rate of Comparative Example 3 are significantly lower than those of Example 1, indicating that it is difficult to obtain a positive electrode material with high capacity and high capacity retention rate if element doping is not performed during the precursor preparation process;
[0134] Comparing Example 1 with Comparative Example 4, the capacity and cycle retention rate of Comparative Example 4 are significantly lower than those of Example 1, indicating that O2 phase lithium cobalt oxide has better electrochemical performance than T2&O2 phase composite lithium cobalt oxide.
[0135] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An O2 phase lithium cobalt oxide positive electrode material, characterized in that: The chemical formula of the lithium cobalt oxide positive electrode material is Li a Na b Co c M d A e O 2-f X f , M is selected from any one or more of Mg, Al, W, Ti, La, Zr, Y, Ni, Mn, K, and Te, A is selected from any one or more of Mg, Al, W, Ti, La, Zr, Y, Ni, Mn, K, and Te, and X is selected from at least one of B, F, and Cl, wherein 0.9≤a≤1, 0≤b≤0.01, 0.95≤c≤1, 0≤d≤0.05, 0≤e≤0.01, and 0≤f≤0.
01.
2. The O2 phase lithium cobalt oxide positive electrode material according to claim 1, characterized in that: It also includes at least one of the following technical features (1) to (4): (1) The molar ratio of lithium element to cobalt element in the O2 phase lithium cobalt oxide positive electrode material is 0.9 to 1.0:1; (2) The median particle size Dv50 of the O2 phase lithium cobalt oxide positive electrode material is 5.0 to 8.0 μm; (3) The main peak of the XRD spectrum of the O2 phase lithium cobalt oxide positive electrode material is located at 18.6±0.1°; (4) The ratio of the area of the (002) peak to the area of the (103) peak in the XRD spectrum of the O2 phase lithium cobalt oxide positive electrode material particles is 2.5 to 3.5:
1.
3. A method for preparing an O2-phase lithium cobalt oxide positive electrode material, characterized in that: include: The mixture is subjected to a first solid phase sintering, wherein the mixture includes sodium, cobalt and M elements, and a sodium cobaltate precursor is obtained after sintering, wherein the molar ratio of the sodium element to the cobalt element in the mixture is 0.65 to 1:1; The sodium cobaltate precursor and the coating material are mixed evenly and then solid-phase sintered for the second time to obtain a precursor with a coating layer, wherein the coating material contains cobalt element and A element; After uniformly mixing the precursor with the coating layer and the first lithium source, molten salt ion exchange is performed, and after impurities are removed, a T2&O2 composite lithium cobalt oxide material is obtained; Dispersing the T2&O2 composite lithium cobalt oxide material and the second lithium source in water to perform a lithium supplementation reaction to obtain an O2 phase lithium cobalt oxide positive electrode material; M is selected from any one or more of Mg, Al, W, Ti, La, Zr, Y, Ni, Mn, K, and Te elements; A is selected from any one or more of Mg, Al, W, Ti, La, Zr, Y, Ni, Mn, K, and Te elements.
4. The preparation method according to claim 3, characterized in that: The cobalt element in the mixture is provided by a first cobalt source, and the first cobalt source is selected from at least one of cobalt tetroxide, cobalt hydroxide, cobaltous hydroxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide; Optionally, the M element is doped into the first cobalt source.
5. The preparation method according to claim 3, characterized in that: The sodium element in the mixture is provided by a sodium source, and the sodium source is selected from at least one of sodium carbonate, sodium hydroxide and sodium bicarbonate.
6. The preparation method according to claim 3, characterized in that: The invention comprises at least one of the following technical features (1) to (10); (1) The sintering conditions of the first solid phase sintering are: heating to 700-900°C at 1-10°C / min and keeping at this temperature for 8-30h; (2) The sintering conditions of the second solid phase sintering are: heating to 500-700°C at 1-10°C / min and keeping at this temperature for 8-30h; (3) The conditions for molten salt ion exchange are: heating to 180-300°C at 1-10°C / min and keeping warm for 0.5-12h; (4) The first lithium source is composed of at least two of LiNO3, LiCl, Li2CO3, LiOH, Li2SO4, Li3PO4, and CH3COOLi; (5) The molar ratio of the lithium element in the first lithium source to the sodium element in the precursor having the coating layer is 1.4 to 20:1; (6) The mass ratio of the T2&O2 composite lithium cobalt oxide material to the second lithium source is 1:2-3; (7) The mass ratio of the T2&O2 composite lithium cobalt oxide material to water is 2-3:14-20; (8) the second lithium source is selected from at least one of lithium hydroxide, lithium carbonate and lithium chloride; (9) The cobalt element in the coating material is provided by a second cobalt source, and the second cobalt source is selected from at least one of cobaltous hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate and cobalt oxyhydroxide; (10) The A element in the coating material is provided by a compound containing the A element.
7. The preparation method according to claim 3, characterized in that: The impurity removal method includes: washing the molten salt ion exchange product with water and then drying it to obtain a T2&O2 composite lithium cobalt oxide material.
8. The preparation method according to claim 3, characterized in that: After the lithium replenishment reaction, the finished product is extracted from the mixed system. The extraction methods include: solid-liquid separation, water washing and drying.
9. A positive electrode, characterized in that The active component thereof comprises the O2 phase lithium cobalt oxide positive electrode material as claimed in claim 1 or 2, or the O2 phase lithium cobalt oxide positive electrode material prepared by the preparation method as claimed in any one of claims 3 to 8.
10. A battery, characterized in that: Comprising the positive electrode as claimed in claim 9.
Citation Information
Cited By
O3-phase lithium cobalt oxide positive electrode material and preparation method and application thereof
CN120955112A
O2-phase lithium cobalt oxide positive electrode material and preparation method and application thereof
CN121134846A
O2-phase lithium cobalt oxide positive electrode material and preparation method thereof, secondary battery and electric device
CN121269822A